Learning in the Intimacy of the Guru-Disciple Relationship: The Case of Mother Amma and her Finnish Follower - Mällinen, Tiina-Mari; Utriainen, Terhi (Approaching Religion, 2024)
Our article has two aims: first, to track the ethos of learning and the importance of the guru–disciple relationship in the Amma movement, and secondly, to explore the ways in which one Finnish disciple frames her life though this special relationship. The narrative of the disciple becomes especially interesting in that she is a long-term devotee from Finland who has a background in formal academic learning and works in a socially highly valued and demanding profession – and yet has chosen to invest a considerable amount of time and energy to spirituality and committed herself to a close and intimate guru–disciple relationship that guides her personal and work life as well as her overall understanding of learning. Our case study, drawing especially on such materials as Amma’s public discourse and one extensive individual narrative, complemented by ethnographical observations in the ashram in India, shows how pervasive the language and ethos of learning can be in a spiritual context, and what the intimacy of the teacher–student relationship may provide to highly educated individuals in contemporary largely secular Western society.